Advancing Legal Preparedness through the Global Health Security Agenda. Issue 1 (2022) - Ayala, Ana; Brush, Adam; Chai, Shuen; Fernandez, Jose; Ginsbach, Katherine; Gottschalk, Katie; Halabi, Sam; Hosangadi, Divya; Mapatano, Dawn; Monahan, John; Moretti, Carla; Pillinger, Mara; et al.
Abstract: The Global Health Security Agenda (GHSA) is a multilateral, multisectoral partnership comprised of more than 70 countries, international organizations, foundations, and businesses to strengthen global health security.